Proxemics. On the semiotics of space during the COVID-19 pandemic - Migliore, Tiziana (E|C, 2021)
Our article focuses on the invisible bubbles of physical closeness and distancing, that normally constitute each person's territory and the intersubjective space, for how they have been deeply altered since the outbreak of the pandemic. COVID-19 has highlighted this silent interpersonal language, studied by proxemics and made of spatial attitudes and behaviour, by preventing any kind of physical contact. Starting from Paolo Fabbri's investigations on “proxemics” and after a specific seminar in Urbino, we will revisit the issue here. In particular, we will examine the new forms of greeting and the ancient relation between greetings and health wishes.